The Spherical-Radial Model for Filtration of Non-Newtonian Oils - Dadashzade, Kh.I.; Mammadova, F.H. (Herald of Azerbaijan Engineering Academy, 2025)
Recently, various models have been used in newly discovered fields depending on the thickness of the reservoir. Through modeling, parameters such as reservoir permeability, production, and pressure distribution are calculated. Using models allows the study of physical processes by varying different parameters and helps confirm theoretical concepts. Improving models brings us closer to real processes. Mathematical expression and optimization of practical problems are also carried out through modeling.